Effects of dietary selenium nanoparticles, selenomethionine and sodium selenite on growth performance, levels of thyroid hormones and antioxidant status of rainbow trout, Oncorhynchus mykiss - Fardin Shaluei; Somayeh Hadadi; Shafigh Shafiei; Hossein Rahimi; Mehrdad Fattollahi (تغذیه آبزیان)
Introduction:Dietary Selenium (Se) is vital for the growth and immune system of fish. The most important action of Se biological functions comes from several specific selenoproteins, some of which are involved in thyroid hormone metabolism, while others play an antioxidant defence role. Se as a nutritional element is obtained in the aquatic environment from two main sources: feed and fertilizer. Fish species absorb dietary Se in various forms, such as organic and inorganic. It should be used in the correct dosage and anything above this can have negative consequences. As for Se in the diet of fish, there are a few different forms commonly used as inorganic, such as Na2SeO3 or sodium selenite. Organic forms of dietary Se also include selenomethionine (SeMet) and selenocysteine (SeCyst). This study was performed to evaluate the effect of different sources of Se on growth performance, activity of antioxidant enzymes and thyroid hormones in rainbow trout.Materials and methods:Organic Se (Se methionine), mineral Se (sodium selenite) and nanoselenium were added to the basal diet at a rate of 0.3 mg/kg. Basal food without Se compounds was used as a control treatment. Fish with an average weight of 29.25 ± 1.70 g were fed with experimental diets for 8 weeks. The fish were fed twice a day (at 9:00 AM and 2:00 PM) at the rate of 4% of their biomass.Results and discussion: The results showed that selenium nanoparticles had no significant effect on growth indices compared to organic and inorganic forms (p<0.05). The activities of superoxide dismutase and catalase enzymes in treatments containing different forms of Se was significantly higher than in the control (p<0.05). The level of malondialdehyde in the liver of fish fed the diet containing sodium selenite was significantly lower than the other experimental treatments (p<0.05). The amount of triiodothyronine in treatments containing selenomethionine and Se nanoparticles was significantly higher than in the control group (p<0.05), which may be due to the stimulation of thyroid stimulating hormone. Thyroxine was not significantly different in fish fed with different forms of Se and in control (p>0.05).Conclusions: In general, using organic, mineral and nanoselenium sources with a concentration of 0.3 mg/kg of diet has strengthened the antioxidant status of rainbow trout fry, and also through the metabolism of triiodothyronine, it has improved the function of the thyroid gland.